Frequency of Fluid Overload Utilizing Body Composition Monitor Versus Clinical Assessment by Nephrologist. - Said, Hafiz Usman; Sabir, Omer; Riaz, Muhammad Mohsin; Dilawar, Mubashir; Zafar, Anjum; Tariq, Fauzia; Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2021)
Bio impedance analysis is a new tool to provide better assessment of fluid status in hemodialysis population with clinical implication. Material And Methods: Descriptive cross sectional study conducted at five hemodialysis centers, Lahore. Patients were assessed for fluid status by body composition monitor (BCM) and two consultant nephrologists before hemodialysis session. Results: Total of 150 consecutive patients were assessed. 80 (53.33 %) were male and 70 (46.67 %) were female. BCM revealed fluid overload in 66 patients ( 44 %) however there was no fluid overload in 84 patients. Among 149 patients , 86 patients (57.71 %) had concordance and agreement between clinical and BCM assessment. While same number of patients ( n=86 i-e 57.71 %) had agreement and concordance with pre dialysis weight gain when assessed clinically by nephrologists . In total 73 patients ( 48.99% ) there was concordance between pre dialysis weight gain and BCM assessment. All three modalities i-e BCM , clinical assessment and pre dialysis weight gain were on the same page in terms of volume status in 55 patients ( 36.9 % ) .Majority of Patients (82 i-e 55.033 %) had weight gain between 1 to 3 kg . CONCLUSION: Body composition monitoring is a useful and comparable tool to conventional clinical methods in assessing the fluid status of patient. In under developed countries, BCM could be a useful tool to assess fluid status of dialysis patients where there is a paucity of trained nephrologists and clinicians.